THE DIFFERENCES BETWEEN THE FIRST PREFERRED BIOLOGICAL DMARD AND THE DRUG SURVIVAL IN GERIATRIC AND YOUNGER ADULT POPULATION WITH RHEUMATOID ARTHRITIS AND PSORIATIC ARTHRITIS: TREASURE REAL-LIFE DATA - Gonullu, E.; Kalyoncu, U.; Yagiz, B.; Ates, A.; Kucuksahin, O.; Bilge, S. Yasar; Kiraz, S. (Elsevier, 2022)
[Abstract Not Available]
Annual European Congress of Rheumatology (EULAR) -- JUN 01-04, 2022 -- Copenhagen, DENMARK